Investigasi Struktur Bangunan Cagar Budaya di Kota Semarang (Indonesian Journal of Civil Engineering Study, 2024)
This research aims to examine and analyze the structure of cultural heritage buildings to ensure sustainability and identify potential damage that may occur. Given the high historical and architectural value, preserving cultural heritage buildings is very important. A comprehensive evaluation was carried out on several cultural heritage buildings in Indonesia using non-destructive methods such as laser scanning, georadar and material strength testing. Laser scanning is used to create accurate 3D models of buildings, while georadar is useful for detecting invisible internal damage. Material strength testing is carried out to assess whether building materials are still suitable or have experienced degradation. The results of the analysis show that many cultural heritage buildings have experienced significant structural degradation due to age, environmental conditions and inappropriate human intervention. Some buildings show cracks in walls and foundations due to land subsidence or extreme climate change. Apart from that, the use of inappropriate restoration materials also contributes to a decrease in the quality of the building structure. This research reveals that routine care and maintenance is necessary to prevent further damage. Therefore, strategic recommendations for the restoration and conservation of cultural heritage buildings are presented in this research. These recommendations include the use of appropriate restoration materials, the application of modern technology in regular monitoring of building conditions, as well as training for conservators and architects in appropriate conservation techniques. It is hoped that this study will become a reference for conservators, architects and related parties in efforts to preserve cultural heritage. In this way, cultural heritage buildings can continue to be preserved and continue to be enjoyed by future generations. Further research is needed to develop more effective and efficient conservation methods to face future challenges.
Keywords: Preservation; Cultural Heritage; Semarang